THE SYSTEM OF UNIVERSITY PUBLISHING PROCESS: THE STRUCTURE AND IT’S ELEMENTS - GALINIENĖ, GINTARĖ (Knygotyra, 2015)
In this article the structure and elements of Lithuanian universities publishing process and its publishing stages as continuous university publishing process are analysed. The preparation of the publishing consists of two main stages: 1) the stage before publishing, when publication is approbated by academic commission and 2) the stage of preparedness, when publication is delivered to the press and is preparing to publish. One of the most important elements of the first stage is the approbation in the academic institution structural department, which helps to keep high purport quality of academic and studies publications. Further stages of publication are general – publication is editing, correcting and doing layout. The structure of university publishing process and its elements (actions) – stage before publishing and stage of preparedness – are handled like a solid and continuous system of publishing process. The general system of universities publishing process is typical and fits to all Lithuanian academical institutions, but typical system of universities publishing process, even if it is solid and continuous, still is not explicated because of long lasting stage before publishing and sta- ge of preparedness.